Maintenance of cellular proliferation by adenovirus early region 1A in fibroblasts conditionally immortalized by using simian virus 40 large T antigen requires conserved region 1. - Riley, T E (1990)
Various mutants of adenovirus E1A were assayed for their ability to complement the growth defect at the nonpermissive temperature for the cell line tsa14 which was isolated by immortalizing rat embryo fibroblasts with the thermolabile large T antigen of tsA58. This cell line grows indefinitely at the permissive temperature but undergoes rapid growth arrest upon shift up to the nonpermissive temperature. Since this growth arrest can be overcome by introduction of wild-type simian virus 40 large T antigen, human papillomavirus 16 E7, and adenovirus E1A, the tsa14 cells provided an excellent system for defining regions of E1A necessary for complementation of the growth defect. We demonstrate that conserved region 1 (CR1) is the region of E1A required for complementation. While CR2 of E1A has been shown to be required for the immortalization of primary cells and is also necessary for the binding of the 105-kDa retinoblastoma protein, mutations within this region did not abrogate complementation of the growth defect. However, since both CR1 and CR2 have previously been shown to be absolutely required for immortalization of primary cells by adenovirus E1A, this evidence suggests that the tsa14 system assays for the maintenance of proliferation and that this requires CR1.